2013
DOI: 10.1186/1472-6963-13-66
|View full text |Cite
|
Sign up to set email alerts
|

Design of the DISCovery project: tailored work-oriented interventions to improve employee health, well-being, and performance-related outcomes in hospital care

Abstract: BackgroundIt is well-known that health care workers in today’s general hospitals have to deal with high levels of job demands, which could have negative effects on their health, well-being, and job performance. A way to reduce job-related stress reactions and to optimize positive work-related outcomes is to raise the level of specific job resources and opportunities to recover from work. However, the question remains how to translate the optimization of the balance between job demands, job resources, and recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 44 publications
0
18
0
1
Order By: Relevance
“…Niks et al ( 2013 , 2018 ) communicated the results of a survey about psychosocial diagnoses, Schneider et al ( 2019 ) communicated work system factors and mental well-being and the Weiner et al’s ( 2020 ) study communicated about the psychological mechanism of stress. In the interventions of Niks et al ( 2013 ) and Schneider et al ( 2019 ), preventive measures were not explicitly communicated, but HCWs discussed potential solutions and defined a plan with concrete measures, while the communication of Weiner et al ( 2020 ) about prevention referred to useful behaviour during stressful situations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Niks et al ( 2013 , 2018 ) communicated the results of a survey about psychosocial diagnoses, Schneider et al ( 2019 ) communicated work system factors and mental well-being and the Weiner et al’s ( 2020 ) study communicated about the psychological mechanism of stress. In the interventions of Niks et al ( 2013 ) and Schneider et al ( 2019 ), preventive measures were not explicitly communicated, but HCWs discussed potential solutions and defined a plan with concrete measures, while the communication of Weiner et al ( 2020 ) about prevention referred to useful behaviour during stressful situations.…”
Section: Resultsmentioning
confidence: 99%
“…The primary goal of all 17 interventions was to reduce or prevent SRDs and thus to change behaviour. Informing HCWs about SRDs was part of the intervention goal; some studies gave information during training (Arrigoni et al 2015 ), digitally (Blake et al 2020 ; Ketelaar et al 2013a , b ; Shanafelt et al 2014 ; Weiner et al 2020 ), during discussion sessions (d'Ettorre and Greco 2015 ; Di Tecco et al 2020 ; Niks et al 2013 , 2018 ; Uchiyama et al 2013 ) or by the occupational physician (Gartner et al 2011 , 2013 ; Ketelaar et al 2013a , b , 2014a , b ; Ruitenburg et al 2015 , 2016 ). Through the giving of information, in all interventions HCWs were encouraged to take action to protect their health, but they could decide this for themselves, or they could decide not to do anything about it.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the articles were from after 2010, possibly showing a growing interest in this topica trend easily confirmed by performing a similar search today. Three trials (Spoor 2010;Gómez-Gascón 2013;Niks 2013) were ongoing at the time; of these, only Niks et al's results have been made available (Niks…”
Section: The Results Of the Searchmentioning
confidence: 99%
“…Added inspiration may be found in studies that have shown the efficacy of healthy lifestyle interventions implemented through community centers 40 and in the workplace. 41,42 Russell et al 40 find that healthy behavioral changes are most often adopted when personal, interpersonal, and programmatic connections are integrated with community-level actions into an overall service delivery framework.…”
Section: Influence Of Occupant Behaviors On Iaqmentioning
confidence: 99%